Money: A market microstructure approach - Malte Krueger (Research On Money in the Economy (ROME), 2008)
The current discussion about the future of the financial system draws heavily on a set of theories known as the 'New Monetary Economics'. The New Monetary Economics predicts that deregulation and financial innovation will lead to a moneyless world. This paper uses a market microstructure approach to show that a common medium of exchange that serves as unit of account will remain a necessary instrument to reduce transaction costs. This finding is supported by empirical evidence from foreign exchange markets.
Keywords: E42; E44; G20; 330; New monetary economics; monetary separation; market microstructure theory; monetary theory; moneyless world; financial innovation